Cholinergic Synapse Pathway Gene Polymorphisms Associated With Late-Phase Responses in Allergic Rhinitis - Samra, Simranjit K.; Rajasekaran, Ashwini; Sandford, Andrew J.; Ellis, Anne K.; Tebbutt, Scott J. (Frontiers in Allergy, 2021)
Allergic rhinitis (AR) is characterized by an early-phase response (EPR), and in a subgroup of individuals, a late-phase response (LPR). We sought to investigate polymorphisms in cholinergic synapse pathway genes, previously associated with late-asthmatic responses, in the LPR. Twenty healthy participants and 74 participants with AR underwent allergen exposure using the Environmental Exposure Unit. Allergic participants were sub-phenotyped using self-reported nasal congestion scores; congestion is the predominant symptom experienced during the LPR. Acute congestion (AC, n=36) participants developed only an EPR, while persistent congestion (PC, n=38) participants developed both allergic responses. We interrogated blood samples collected before allergen exposure with genotyping and gene expression assays. Twenty-five SNPs located in ADCY3, AKT3, CACNA1S, CHRM3, CHRNB2, GNG4, and KCNQ4 had significantly different allele frequencies (P < 0.10) between PC and AC participants. PC participants had increased minor allele content (P = 0.009) in the 25 SNPs compared to AC participants. Two SNPs in AKT3 were associated with gene expression differences (FDR < 0.01) in PC participants. This study identified an association between the LPR and polymorphisms in the cholinergic synapse pathway genes, and developed a novel method to sub-phenotype AR using self-reported nasal congestion scores.